DEVELOPING AN EDUPRENEURSHIP SCHOOL BASED APPLICATION FOR TEACHING READING AT SMPN 3 SIKUR IN THE ACADEMIC YEARS OF 2024-2025 - M. Juzi Alfan Hidayat; Dira Permana; Abdul Kadir Bagis (Sinar Lima, 2026)
This study aimed to develop a digital learning product that integrates English reading instruction with entrepreneurship education for junior high school students. Employing a Research and Development (R&D) approach, the study resulted in a hybrid digital learning platform named My Edu-Preneurship, which is available as an Android-based application (APK) and a web-based platform accessible via iPhone and Windows devices. The development process was grounded in a needs analysis conducted through questionnaires distributed to 28 seventh-grade students of class VII C at SMPN 3 Sikur in the 2024–2025 academic year. The findings revealed that students strongly prefer digital learning media that are accessible, used-friendly, visually engaged, and aligned with their learning level. Students also expressed positive responses toward structured reading materials, interactive exercises, and the integration of entrepreneurship-related content. Based on these needs, the platform was designed to provide level-appropriate reading materials embedded with fundamental entrepreneurial concepts to enhance both reading comprehension and entrepreneurial awareness. The hybrid system ensures flexible access across various devices, supporting inclusive and technology-based learning environments. Expert validation confirmed that the product meets pedagogical, visual, design, and technical standards. Overall, My Edu-Preneurship is considered a relevant and effective digital learning solution that supports literacy development and entrepreneurship education for seventh-grade students in contemporary educational contexts.